Thorium and fetal neural tube defects: an epidemiological evidence from large case-control study - Bin Wang (BMC, 2021)
Abstract Background Thorium is ubiquitous in the environment and its relationship with birth defects is still under discussion. This study aimed to investigate the associations of maternal exposure to thorium with risk of neural tube defects (NTDs) by using a case–control study, as well as the relationship between thorium exposure and the indoor air pollution from coal combustion. Methods This study was conducted in 11 local healthcare hospitals during 2003–2007 in Shanxi and Hebei provinces, China. A total of 774 mothers were included as participants who delivering 263 fetuses with NTDs including 123 with anencephaly, 115 with spina bifida, 18 with encephalocele, and 7 other NTD subtypes (cases), and 511 health fetuses without NTDs (controls). Their hair samples were collected as close as to the occipital posterior scalp, of which those grew from 3 months before to 3 months after conception was cut to measure the thorium concentration by inductively coupled plasma-mass spectrometry. Results We found a higher hair thorium concentration in the total NTD cases with 0.901 (0.588–1.382) ng/g hair [median (inter-quartile range)] than that in the controls with a value of 0.621 (0.334–1.058) ng/g hair. Similar results were found for the three concerned NTD subtypes. Maternal hair thorium concentration above its median of the controls was associated with an increased risk of the total NTDs with an adjusted odds ratio of 1.80 [95% confidence interval (CI), 1.23–2.63)] by adjusting for all confounders. There was obvious dose-response relationship between maternal hair thorium concentration and the risk of total NTDs, as well as their two subtypes (i.e. anencephaly and spina bifida). Maternal hair thorium concentration was positive associated with their exposure level to indoor air pollution from coal combustion during cooking. Conclusions Overall, our findings revealed that maternal periconceptional thorium exposure was associated with the risk of NTDs in North China. Reducing the coal usage in the household cooking activities may decrease maternal thorium exposure level. Graphical abstract